Virtual Coaching As An Innovative Supervision Model: Improving Teacher Competence Through A Technological Approach In The 5.0 Era - Sahudi Sahudi (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
Technological advances in the Society 5.0 era demand innovation in the implementation of educational supervision to make it more adaptive and sustainable. This study aims to examine the effectiveness of Virtual Coaching as an innovative supervision model in improving teacher competency. The study used a qualitative approach with a case study method, chosen to gain an in-depth understanding of the implementation of Virtual Coaching in a real-world context. The research location was selected at MTs. Kanjeng Sepuh Sidayu Gresik because this madrasah has implemented technology-based supervision and demonstrated institutional readiness in developing teacher competency digitally. The study was conducted over six months, with data sources including the madrasah principal, teachers, and educational supervisors. Data collection techniques were carried out through in-depth interviews, participatory observation, and document analysis. Data validity was maintained through triangulation of sources and techniques, while data analysis was conducted using a qualitative descriptive analysis model that includes data reduction, data presentation, and drawing conclusions. The results showed that Virtual Coaching provided flexibility in supervision, improved teachers' pedagogical skills in utilizing learning technology, and accelerated the process of providing feedback from supervisors to teachers. Teachers also showed increased involvement in ongoing professional development. Obstacles identified included limited access to technology and differences in digital literacy levels among teachers. This study concludes that Virtual Coaching is an effective supervision model in supporting the improvement of teacher competency in the digital era, with recommendations for strengthening technological infrastructure and digital literacy training for teachers to optimize its implementation.